Intervenciones de enfermería y su influencia en la prevención del embarazo no deseado en la adolescencia. Centro de Salud Balzar de Vinces. Vinces. Los Ríos. octubre 2018 - abril 2019 - Santillan Ortega, Luis Ricardo (2019)
The unwanted pregnancy in adolescence is conceived as young people initiate their sexual life inappropriately and without responsibility, letting themselves be carried away by the experimentation of desire, with this project it is possible to investigate, explain and raise awareness of everything related to unwanted pregnancy in Adolescence itself, strategies are proposed to lower the rate of this problem through the intervention of nursing staff. General objective: to determine the interventions of nursing and its influence as prevention to reduce the rate of unwanted pregnancy in adolescence of the population of the Health Center "Balzar de Vinces". Vinces. The rivers. October 2018 - April 2019. Methodology: the deductive, inductive and logical historical method applying a mixed qualitative-quantitative approach, being a descriptive, applied, field and transversal research. For data collection it is used as a questionnaire of structured questions. Results: the data were analyzed in the Microsoft Excel program where it was observed that the nursing staff is not fulfilling the role of health promotion since 62% of the adolescents state that they do not receive sex education talks and 71% He has already started his sexual life. Conclusion: when performing the analysis, we obtained statistically significant results that allowed us to accept the hypothesis where the high rate of unwanted pregnancies in adolescence is related to poor nursing interventions.